Variação temporal e espacial da composição da ictiofauna demersal do infralitoral roso da baía de Paranaguá, PR, Brasil - 2004 - Nakayama, Paula (Universidade Federal de São Carlos, 2004)
The ichthyofauna of Paranagua bay infralittoral was studied from samples obtained from five sampling points, respectively in front of Gamboa dos Papagaios, Gamboa do Sucuriu, Gamboa do Baguaçu, Planície da Ponta do Poço and Praia do Pontal do SuI. The samples were collected monthly, from October 1999 to September 2000, with a trawl net. As a result, 6633 individuals, from 55 species and 27 families were captured, and the madamango sea catfish (bagre) Cathorops spixxi was the most abundant element with 21% of the total number. During the sample collection, the most important variable for the distribution of months was the temperature, which allowed the division of the sampling period into hot and cold months. A detected variation in groupings reflected the temporal oscillation of the ichthyofauna composition, and the variation in dissimilarity between sampling points occurred due to the differences in abundance and richness of the captured species. The highest percentages of dissimilarity between sampling points were observed during the hot months, and the high frequencies of Anisotremus surinamensis, Etropus crossotus, Genidens genidens, Micropogonias fumieri, and Sphoeroides greeleyi were also related to high temperatures. Since a great number of species present a more intense reproductive activity during high temperature periods, and some marine species use the estuary as a rearing ground, a higher number and richness of fishes could be observed during the hot months. Finally, the analysis of the ichthyofauna space variation showed differences in composition and abundance of fish communities from the studied areas. These space differences are probably related to the complexity of the habitats, which is caused by the different bottom covers found at the sampling points.
Keywords: Peixe; Complexo estuarino Maía de Paranaguá (PR); Infralitoral; CIENCIAS BIOLOGICAS::ECOLOGIA